Text Steganography in Videos Using Ascii Code Values - Hassan, Ahmed Mahmoud; Fadel, Hassan Abdulhadi; Belibas, Mohammed Muntazir Rushdi; Abdul Sada, Mohammed Jassim; Dhahi, Estqlal Hammad; Abdulmunem, Ashwan A.; Harjan, Zahraa A. (KJCT, 2025)
Text steganography is a technique used in digital video files to conceal text. Sensitive information, such passwords or messages from outside parties, has long been hidden using this method. Depending on the user's intention, text steganography can be used for both good and bad things. The procedure is adding brief textual captions to each frames in a video file without appreciably altering the film's overall size or look. Next, an algorithm is used to encrypt the embedded data, making it difficult for unauthorized users to access and perhaps intercept the transmission. This technique makes it possible to send encrypted messages securely via networks without being discovered by outsiders trying to obtain private data that is hidden in videos that they are not allowed to watch. Through digital media platforms like YouTube or Video, text steganography offers businesses and individuals alike an efficient method to safeguard their data while still securely sharing it with others. Because only people with the ability to decode secret texts will be able to access them once they are embedded into a video file format, it also gives them more control over the kind of content they publish online. In this paper a new approach for hiding ASCII code values in videos has been tested and evaluated which presents an acceptable result in this field.